Development of siRNA therapeutics to combat microbial infections: a bibliometric analysis - He, Yi; Yuan, Yulin; Zhou, Meihua; Li, Miao; Li, Lingjin; Li, Chunhong; Liang, Xiaocui; Liu, Panyan; Wang, Wei; Deng, Zhenfeng (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundThe rise of antimicrobial resistance and the COVID-19 pandemic highlight the limitations of traditional therapies. Small interfering RNA (siRNA) therapeutics, which utilize RNA interference for targeted gene silencing, present a promising approach to combating microbial infections. However, research in this area remains fragmented. This study employs a comprehensive bibliometric analysis to chart research trends and inform future directions.MethodsA total of 8,426 publications from the Web of Science Core Collection (2001–2025) were analyzed using CiteSpace and VOSviewer software to examine annual publication trends, geographic and institutional contributions, author networks, journal impacts, and keyword evolution. Data extraction focused on English-language articles.ResultsThe publication trends for siRNA therapeutics in microbial infections have evolved in three phases: rapid growth, stabilization at a peak, and subsequent cyclical fluctuations. Research contributions spanned 99 countries and regions, with 5,564 institutions and 1,234 journals involved. China (2,849 publications) and the United States (2,820 publications) led in publication volume. While the United States maintained dominance in academic influence and collaboration, China has steadily increased its research output in this area. The Journal of Virology emerged as the leading journal in terms of both productivity and citation impact. Key research areas include delivery systems, target selection, manufacturing technologies, antiviral therapeutics, and combination therapies. The field has shifted from basic mechanistic studies to clinical applications, with future research poised to focus on organ-specific delivery beyond the liver, exploration of diverse administration routes, integration of artificial intelligence-driven strategies, and enhanced global collaboration.ConclusionThis bibliometric analysis offers a comprehensive overview of siRNA therapeutics for microbial infections, highlighting collaboration networks and academic influence across authors, countries, institutions, and journals. The study provides valuable insights into current research trends and serves as a foundational reference for guiding future collaborative efforts and innovations in this field.